Argyria after silver nitrate intake: Case report and brief review of literature - Alma Ileana Molina-Hernandez; Jose Manuel Diaz-Gonzalez; Marcela Saeb-Lima; Judith Dominguez-Cherit (Wolters Kluwer Medknow Publications, 2015)
Argyria is a condition characterized by pigmentary changes secondary to exposure to silver salts and its accumulation in skin, mucous membranes and annexes, which typically produces blue or gray-blue spots. A case of a male patient 62 years old, previously healthy, who has a blue-gray hyperpigmentation on the face, trunk and upper extremity, affecting sun-exposed areas is presented. He admitted having ingested silver nitrate for 5 years at a rate of 1 bottle per week, with the intent to kill microorganisms in his body.